Exogenous Enzymes and the Digestibility of Nutrients by Broilers: A Mini Review - Alabi , O.O.; Shoyombo, A.J.; Akpor, O.B.; Oluba, O.M.; Adeyonu, A.G. (International Journal of Poultry Science, 2019)
The feed fed to broilers is a determinant of digestibility, absorption and utilization of nutrient by the birds. The increasing cost of poultry production currently for feed formulated from conventional feed ingredients has made the use of cheaper, lesser known and unconventional feed ingredients a possible way of reducing the cost of production and providing more profit to poultry producers. However, most of the alternative feed ingredients are richer in Non-Starch Polysaccharide (NSP) content, the high content of NSP invariably affect animals’ performance in different ways. To mitigate the anti-nutritional factors of NSP, the use of feed enzymes are employed. This is so, since the endogenous enzyme secreted in the gastro-intestinal tract of broilers cannot digest NSP, therefore, it is desirable to supplement high fibrous feed with exogenous enzymes for effective and efficient digestion of NSP content and better performance of the birds in terms of feed intake, growth rate, feed conversion efficiency, body weight gain and carcass characteristics. These exogenous enzymes are readily obtainable from different microorganism such as Bacillus subtilis, Trichoderma longibrachiatum, Aspergillus niger, Trichoderma viride, Humicola insolens. The enzymes preparations are available under various trade names such as Nutrase xyla, Histazyme, Avizyme, Natugrain, Allzyme, Grindazyme, Roxazyme G, Avizyme, Maxi-grain, Natuzyme and others. In this review, exogenous enzyme for broiler’s diet, features of bacterial and fungal xylanase enzymes, effect of xylanase and phytase on broiler nutrition, qualities of commercial enzymes and benefits of enzyme supplementation was discussed.